2002
DOI: 10.1152/jn.00026.2002
|View full text |Cite
|
Sign up to set email alerts
|

Development of GABAA Receptor-Mediated Inhibitory Postsynaptic Currents in Hippocampus

Abstract: Development of GABA A receptor-mediated inhibitory postsynaptic currents in hippocampus. J Neurophysiol 88: 3097-3107, 2002; 10.1152/jn.00026.2002. Hippocampal CA1 pyramidal cells receive two kinetic classes of GABA A receptor-mediated inhibition: slow dendritic inhibitory postsynaptic currents (GABA A,slow IPSCs) and fast perisomatic (GABA A,fast ) IPSCs. These two classes of IPSCs are likely generated by two distinct groups of interneurons, and we have previously shown that the kinetics of the IPSCs have im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…General characteristics of the maturation of GABAergic synapses (Hollrigel and Soltesz, 1997;Dunning et al, 1999;Huntsman and Huguenard, 2000;Banks et al, 2002), including developmental increases in mGPSC frequency, reduction in mGPSC amplitude, and faster kinetics ( Fig. 1G,H; Table 1) were observed in both groups.…”
Section: Postnatal Ee Rearing Enhances Gabaergic Neurotransmissionmentioning
confidence: 81%
“…General characteristics of the maturation of GABAergic synapses (Hollrigel and Soltesz, 1997;Dunning et al, 1999;Huntsman and Huguenard, 2000;Banks et al, 2002), including developmental increases in mGPSC frequency, reduction in mGPSC amplitude, and faster kinetics ( Fig. 1G,H; Table 1) were observed in both groups.…”
Section: Postnatal Ee Rearing Enhances Gabaergic Neurotransmissionmentioning
confidence: 81%
“…First, noradrenergic modulation of intrinsic conductances in interneurons has been repeatedly shown (Bergles et al, 1996;Maccaferri and McBain, 1996, Parra et al, 1998, Banks et al, 2002. Therefore, we wanted to avoid the assumption that modulation of coupling indexes must reflect modulation of the junctional conductance across the pair.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the rate of spontaneous IPSCs mediated by "slow" GABA A receptors (GABA A, slow ) (Pearce, 1993), which may originate from neurogliaform interneurons (Price et al, 2005;Szabadics et al, 2007), has been reported to be selectively increased by low doses of NA (Banks et al, 2002). However, without a parallel effect on coupling, it would be difficult to explain how this powerful excitation of a GABAergic network would not translate into phasic synchronized epileptiform activity.…”
Section: Gap Junctions Of Hippocampalmentioning
confidence: 99%
“…S2 A, available at www.jneurosci.org as supplemental material), consistent with the slow kinetics exhibited by evoked PSCs. The slow kinetics of GABAergic PSCs suggests a dendritic localization of the early GABAergic connections (see Discussion) (Miles et al, 1996;Banks et al, 1998Banks et al, , 2002). These findings demonstrate that GABAergic interneurons are the primary source of synaptic inputs onto immature neurons in the adult hippocampus, similar to what occurs to CA1 pyramidal neurons and DGCs during development (Tyzio et al, 1999;Khazipov et al, 2001;Gozlan and Ben Ari, 2003).…”
Section: The Onset Of Gabaergic Connectivitymentioning
confidence: 97%
“…In contrast, the order of appearance of fast and slow GABAergic afferents in the developing hippocampus has not been clearly established. Although the existence of principal neurons displaying exclusively slow GABAergic PSCs has not yet been confirmed by electrophysiological recordings in the developing hippocampus (Hollrigel and Soltesz, 1997;Banks et al, 2002), anatomical studies indicate that dendritic GABAergic synapses are formed before somatic ones. In a previous study, Lüb-bers and Frotscher (1988) showed that immature DGCs in P5 rats received mostly GABAergic afferents impinging onto dendritic shafts.…”
Section: Similarities Between the Developing And Adult Hippocampusmentioning
confidence: 98%